Question #bf526 Calculus Basic Differentiation Rules Power Rule 1 Answer Homayra · Stefan V. Aug 18, 2017 #dy/dx = 2 * 2x^(2-1) - 4x^(1-1)+ 0 * 9^(0-1) = 4x - 4# #(d^2y)/dx^2 = 1 * 4x^(1-1) - 0 * 4^(0-1) = 4# Explanation: At first, differentiate the equation of #y# and then differentiate the first differentiated equation to find the value of the second derivative. Answer link Related questions How do you find the derivative of a polynomial? How do you find the derivative of #y =1/sqrt(x)#? How do you find the derivative of #y =4/sqrt(x)#? How do you find the derivative of #y =sqrt(2x)#? How do you find the derivative of #y =sqrt(3x)#? How do you find the derivative of #y =sqrt(x)#? How do you find the derivative of #y =sqrt(x)# using the definition of derivative? How do you find the derivative of #y =sqrt(3x+1)#? How do you find the derivative of #y =sqrt(9-x)#? How do you find the derivative of #y =sqrt(x-1)#? See all questions in Power Rule Impact of this question 1344 views around the world You can reuse this answer Creative Commons License